Herbicides and mechanical control of Imperata cylindrica as a first step in grassland rehabilitation - Terry, P.J.; Adjers, G.; Akobundu, I.O.; Anoka, A.U.; Drilling, M.E.; Tjitrosemito, S.; Utomo, M. (Springer, 1996)
This review is prefaced by an introduction to biological characteristics of Imperata cylindrica which relate to its control by chemical and mechanical methods. Of the many herbicides tested and used against I. cylindrica, glyphosate has became the market leader but the potential of imazapyr is also recognized. The activity of additives to improve glyphosate and imazapyr performance is summarised and linked to a review of spray volume rates and the use of three types of application equipment: hydraulic (knapsack) sprayers, spinning discs and weed wipers. An example of the practical use of glyphosate in an estate crop is given. The role of tillage in the management of I. cylindrica is discussed but emphasis is given to pressing as a technique for promoting natural regeneration of forestry species. An integrated approach is considered to be essential for the management of I. cylindrica whereby fire prevention and methods of control are deployed in the conversion of Imperata-dominated land into sustainable, productive systems. Examples are given of integrated management in commodity plantations, rehabilitation of Imperata grasslands through reforestation, and conservation tillage to sustain soil fertility and productivity.